Challenges and opportunities in transitional care process in Behçet’s syndrome - Di Cianni, Federica; Mastrolia, Maria Vincenza; Biancalana, Edoardo; Marinello, Diana; Emmi, Giacomo; Mosca, Marta; Simonini, Gabriele; Talarico, Rosaria (Frontiers in Medicine, 2024)
Behçet's syndrome (BS) is a rare chronic multi-systemic inflammatory disorder that usually involves adults between third and fourth decades of life, while pediatric and juvenile onset are relatively rare. BS young patients (YP) often develop a full-blown disease late after onset, requiring careful diagnostic workup and regular follow-up while they grow up. In this regard, the purpose of transitional programs is to ensure continuous high-quality care to YP with chronic conditions, providing them with the skills necessary to become independent and empowered adults able to chronically self-manage their disease. EULAR/PReS released the first set of standards and recommendations for transitional care (TC) of YP with juvenile-onset rheumatic diseases, but the appropriate timing for transition, the tools to evaluate patients' readiness, and indicators of transition plans effectiveness still need to be identified. Although little is known regarding TC in BS, it is easy to assume that BS YP will benefit from developmentally and disease-specifically appropriate transition plans, which may promote continuity of care, improve perceived quality of life and prevent poor disease outcomes. This perspective article discusses the key concepts and the goals of TC, addressing the potential challenges and opportunities of TC for YP with BS in clinical practice.